Lipid emulsion mitigates intravenous amiodarone toxicity in a rat model. Issue 1 (31st December 2022) - Stewart, Rachael; Newman, Verity; Harvey, Martyn; Tang, Mingtan; Wu, Zimei; Cave, Grant
Abstract: Introduction: Our study investigated whether lipid emulsion therapy could act as an antidote for intravenous amiodarone toxicity in a rat model. Methods: 20 rats were randomised to receive lipid emulsion (ILE) or saline. Rats were infused with amiodarone at 1 mg/kg/min for 20 min. ILE rats then received 6 mL/kg of IV 20% ILE, with controls receiving saline. Amiodarone infusion then recommenced at 0.25 mg/kg/minute for 15 min. Heart rate and mean arterial pressure (MAP) were recorded at the commencement and end of the first amiodarone infusion, and every 5 min during the second amiodarone infusion until experiment termination. Blood was sampled for amiodarone concentration at the conclusion of each infusion. Results: At experiment termination MAP was greater for the ILE group (85 vs 60 mmHg, p = 0.01), with no difference in heart rate between groups (224 vs 232 bpm, p = 0.19). Amiodarone concentration decreased after saline treatment and was stable after ILE (change −6.4 micromol/L saline, 0.11 micromol/L lipid p < 0.001) Conclusions: ILE therapy mitigated intravenous amiodarone-induced hypotension in this rat model. While amiodarone was retained in lipid treated blood the quantum of this increase did not support the "lipid sink" hypothesis. Further research is required to evaluate the clinical relevance of these findings.